Study of the Antagonism Effect of Leuconostoc Spp. against Listeria Monocytogenes (International Journal of Psychosocial Rehabilitation, 2020)
The present study has involved isolation and characterization of Leuconostoc spp. from raw milk, sauerkraut, fresh fruits and vegetables, and the 15 Leuconostoc spp. (7) from raw milk, (5) from fresh fruits and vegetables, and (3) isolated from sauerkraut. All isolates have submitted to the cultural, microscopical, and biochemical tests, also using the Vitek 2 system for identification to species. The fifteen most promising candidates were further characterized and presented antimicrobial activity against Listeria monocytogenes, with putative probiotic potential, suggesting the applicability of sauerkraut fermentations as a source for probiotic isolation. Due to their origin, these strains should be suited for future application in the food industry, namely vegetable products such as sauerkraut itself.